Analisis Faktor yang Mempengaruhi Perkembangan Siswa Usia Sekolah Dasar: Sebuah Tinjauan Pustaka - Irhas, Irhas (CT. Rajawali media Utama, 2024)
The development process of elementary school age students is greatly influenced by various factors, both internal and external. This article aims to describe the factors that influence the development of elementary school students. The type of research used in this research is library research with a qualitative research approach. The library data in this research is secondary or supporting data. The data collection technique in this research is documentation study. The data sources used are books and journals related to the selected topic. The data analysis used in this research is content analysis. Based on the research results, it was found that in general the factors that influence the development of elementary school students are internal factors and external factors. Factors that influence the development of elementary school age students include: Physical development and physical experience of children, intelligence and IQ, children's learning experiences, environmental factors (family environment, play environment, and school environment).